Insomnia and depression among bariatric surgery patients: the chain mediating effect of resilience and anxiety - Si, Jijian; Zhang, Yixin; Li, Manyuan; Liu, Tour (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to examine the psychological mechanisms of depression in both bariatric surgery candidates and post-bariatric surgery patients and to explore the roles of resilience and anxiety in these relationships.MethodsA total of 431 candidates for bariatric surgery were recruited from a hospital. One month after the bariatric surgery, 228 patients continued to participate in the study. All participants completed the Insomnia Severity Index (ISI), Connor and Davidson Resilience Scale (CD-RISC), Generalized Anxiety Disorder 7-item scale (GAD-7), and Patient Health Questionnaire Depression Scale (PHQ-9). A mediation model analysis was used to investigate the mediating role of resilience, the mediating role of anxiety, and the chain mediating role of resilience and anxiety in the relationship between insomnia and depression.ResultsInsomnia positively correlated with depression through the mediating role of resilience, the mediating role of anxiety, and the serial mediating effect of resilience and anxiety among bariatric surgery candidates. However, only a direct effect of insomnia on depression and the mediating role of anxiety were found in post-bariatric surgery patients.ConclusionThe findings demonstrated that insomnia leads to an increase in depression among bariatric surgery patients, with resilience and anxiety playing significant mediating roles. This also highlights the need for targeted resilience-enhancing interventions in obese patients who are about to undergo bariatric surgery.